eCM 2013
DOI: 10.22203/ecm.v025a22
|View full text |Cite
|
Sign up to set email alerts
|

Cell cytoskeletal changes effected by static compressive stress lead to changes in the contractile properties of tissue regenerative collagen membranes

Abstract: Static compressive stress can influence the matrix, which subsequently affects cell behaviour and the cell's ability to further transform the matrix. This study aimed to assess response to static compressive stress at different stages of osteoblast differentiation and assess the cell cytoskeleton's role as a conduit of matrix-derived stimuli. Mouse bone marrow mesenchymal stem cells (MSCs) (D1 ORL UVA), osteoblastic cells (MC3T3-E1) and postosteoblast/pre-osteocyte-like cells (MLO-A5) were seeded in hydrated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…Here, we focused on the use of a mouse bone marrow mesenchymal stem cell source (D1 cell line) and show that in the absence of osteogenic media cells show to differentiate into the osteoblastic lineage. Previous reports support this observation, where mesenchymal stem and osteoblastic cell culture within collagen gels showed to generate internal loads, inside the gels, leading to gel contraction and differentiation towards the osteoblastic lineage 21 22 23 .…”
Section: Discussionsupporting
confidence: 71%
“…Here, we focused on the use of a mouse bone marrow mesenchymal stem cell source (D1 cell line) and show that in the absence of osteogenic media cells show to differentiate into the osteoblastic lineage. Previous reports support this observation, where mesenchymal stem and osteoblastic cell culture within collagen gels showed to generate internal loads, inside the gels, leading to gel contraction and differentiation towards the osteoblastic lineage 21 22 23 .…”
Section: Discussionsupporting
confidence: 71%
“…However, cells in compressed gel develop an ovoid shape and present a close network of numerous actin filaments. The actin filaments in dense gels show a greater tendency toward osteogenic differentiation as compared with hydrostatic gels [70]. Another study showed a similar result for F-actin stress fibers, which become prominent when estrogen was added under mechanical pressure, wherein, alkaline phosphatase activity, an early indicator of osteogenesis, was observed to be higher showing osteogenesis [71].…”
Section: Interventions In Actin Remodeling and Their Effect On Msc DImentioning
confidence: 77%
“…It was found that this reduction in cell tension induced adipogenic rather than osteogenic differentiation, as measured by expression of liposome lipase (adipogenic) as well as ALP and CBFa1 (osteogenic). However, the interdependence between cell morphology and intracellular stress cannot be ignored as it has been shown that the disruption of the cytoskeleton through ROCK inhibition will prevent the formation of cell processes in MC3T3-E1 cells cultured on collagen substrates [75]. Cell morphology has also been shown to affect cell-generated stress, with bovine pulmonary smooth muscle cells and 3T3 mouse fibroblasts both shown to induce higher forces on micropost substrates when allowed to expand to a larger cell area [76].…”
Section: Discussionmentioning
confidence: 99%